APLIKASI PEMBELAJARAN SLOKA DALAM KITAB SUCI BHAGAVAD GITA BERBASIS ANDROID - Machudor Yusman; Made Widhiyana; I Made Sadwika Hare (Jurnal Pepadun, 2022)
Bhagavad Gita Devata Song, is one of the Vedas. He often refers to it as the fifth veda, the Pancamo Veda. It is not clear why it was named so, because when viewed from the aspect of the codification of the Hindu religious scriptures called the Vedas, it is traditionally called Vedic chess. Structurally the content of the Bhagavad-gita is more focused and is a collection of the previous Vedas. This is one step in the development of the history of thinking in Hinduism. The Bhagavad-gita appears as part of the Mahabharata which consists of 18 parvas, and 700 slokas. Learning the Bhagavad Gita is a necessity that must be carried out by Hindu students. Every day, even every time students should take their time to learn to read the Bhagavad Gita. A good learning process is a learning process that can make it easier for students to understand the Bhagavad Gita material being taught. In this study, the information provided by the application includes an understanding of the Bhagavad Gita, the contents of the verse from the Bhagavad Gita, assistance on how to read the sloka properly and correctly according to the existing recommendations. This system provides interactive information in the form based on videos on how to recite the verse Bhagavad Gita, as well as the contents of the verse and its translation.